ERGONOMIC APPLICATIONS IN INDUSTRY - Gempur Santoso (International Journal of Social Science, 2025)
Industry players need to understand about ergonomics, including those who work in industry. In fact, if they understand industrial ergonomics, workers will not get tired easily at work, be safe, comfortable, and have good productivity. Therefore, this article will discuss the understanding of ergonomics in industry. This writing is done descriptively or in an exposition. The data collection method is obtained from several opinions by using literature studies. The conclusion is that in designing an ergonomic industry, four aspects can be guided, namely: anthropometry to create tools according to the user's reach and short work paths, work environment, work psychology, and skeletal muscle physiology at work